Advances in Diagnostic Dermatopathology, from Histopathologic to Molecular Studies - Sakai, Yasuhiro (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on novel findings of diagnostic dermatopathology, such as diagnosable new morphological (histopathologic) findings, immunohistochemical and immunofluorescent markers, and molecular techniques. Dermatopathology is the most sophisticated area in anatomic pathology; we can easily observe superficial skin lesions using our eyes without the need for an invasive approach and can easily compare gross configurations to microscopic and immunohistochemical findings. Meanwhile, dermatopathology has recently focused on the study of various cutaneous diseases at the molecular biology level. Many cutaneous diseases are now being well-researched, and special attention is paid to keratoacanthoma, lichen sclerosus (et atrophicus), mycosis fungoides, atopic dermatitis, epidermolysis bullosa, extramammary Paget's disease, malignant melanoma, psoriasis, and secondary neoplasms associated with nevus sebaceous.